EVALUASI INSTALASI LISTRIK PADA GEDUNG MULTI CENTRE OF EXCELLENT (MCE) RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG - Wahyu Pramon, Eko; Karnoto, Karnoto; Nurhayati, Titik (Elektrika, 2017)
MCE Building Sultan Agung Islamic Hospital Semarang is a public facility that requires an electrical installation system that is in accordance with PUIL 2000. The purpose of evaluating electrical installations at the Multi Center of Excellent (MCE) building in Sultan Agung Semarang Islamic Hospital is to find out electrical installations in accordance with PUIL 2000 Evaluation of electrical installations includes calculation of MCB security and calculation of cable size. Calculation using manual calculation method and calculation using Ecodial Calculation 4.7 software. The calculation results are then compared to the installed units. From the results of the comparison it can be seen whether the electrical installation is in accordance with PUIL 2000. The results of the analysis can be concluded that the electrical installation system in the MCE building of Sultan Agung Semarang Islamic Hospital is in good condition and safe. In MCB installed units, they are in accordance with the PUIL 2000 standard. In the cable sizes installed several are in a condition not in accordance with the PUIL 2000 standard so cable replacement is required. For example, on the 1st floor divider panel SDP cable where the installed cable is 4x35 mm2, it is replaced by 4x95 mm2.Keywords: Evaluation of Electrical Installation, PUIL 2000, Ecodial Advance Calculation 4